2014
DOI: 10.1111/1471-0528.12803
|View full text |Cite
|
Sign up to set email alerts
|

Variation of urinary protein to creatinine ratio during the day in women with suspected pre‐eclampsia

Abstract: Objective To investigate the stability throughout the day of the protein to creatinine ratio (PCR) in spot urine, to demonstrate whether the PCR is a valid alternative for 24-hour protein investigation in pregnant women.Design Prospective study.Setting Tertiary referral university centre.Population Women suspected of having pre-eclampsia, admitted to the Erasmus Medical Centre.Methods Twenty-four-hour urine collections and simultaneously three single voided 5-ml aliquots were obtained at 8 a.m., 12 a.m. (noon)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(19 citation statements)
references
References 17 publications
(23 reference statements)
0
18
0
1
Order By: Relevance
“…Lindheimer and Kanter [ 28 ] discussed the complexities of assessing proteinuria in pregnancy and notably whether protein excretion remains constant over 24 hours, which may impact significantly on the reproducibility of the protein/creatinine ratio at different time points. A recent study assessed serial protein creatinine ratio (PCR) measurements in a 24-hour period and showed that the PCRs correlated strongly with each other and with the 24-hour protein excretion but did show variation throughout the day [ 29 ]. Women with underlying renal disease with pre-existing proteinuria, with or without hypertension, are at high risk of developing pre-eclampsia, yet diagnosis in this group is particularly challenging.…”
Section: Complexities Of Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Lindheimer and Kanter [ 28 ] discussed the complexities of assessing proteinuria in pregnancy and notably whether protein excretion remains constant over 24 hours, which may impact significantly on the reproducibility of the protein/creatinine ratio at different time points. A recent study assessed serial protein creatinine ratio (PCR) measurements in a 24-hour period and showed that the PCRs correlated strongly with each other and with the 24-hour protein excretion but did show variation throughout the day [ 29 ]. Women with underlying renal disease with pre-existing proteinuria, with or without hypertension, are at high risk of developing pre-eclampsia, yet diagnosis in this group is particularly challenging.…”
Section: Complexities Of Diagnosismentioning
confidence: 99%
“…Delivery recommendations from NICE [ 29 ] suggest conservative management below 34 weeks’ gestation and urge that elective delivery before 34 weeks not be considered. The American College of Obstetricians and Gynecologists taskforce bulletin [ 35 ] states that, for women with mild gestational hypertension or pre-eclampsia without severe features, delivery at 37 weeks, rather than continued observation, is indicated.…”
Section: Deliverymentioning
confidence: 99%
“…However, no differences among the three measurements with respect to sensitivity (89–96%) and specificity (75–78%) to predict proteinuria were found. 43 A systematic review concluded that the spot protein:creatinine ratio is a reasonable ‘rule out’ test for significant proteinuria during pregnancy because of its high sensitivity and low negative likelihood ratio (0.12). 44 Of note, although the presence of proteinuria can aid in the diagnosis of pre-eclampsia, the severity of proteinuria has limited prognostic value 45 and, consequently, severe proteinuria has been removed from the diagnostic criteria for severe pre-eclampsia by some professional organizations.…”
Section: Diagnosis Of Pre-eclampsiamentioning
confidence: 99%
“…Numerous obstetric societies recommend using it as a diagnostic test with a cut‐off of around 30 mg/mmol; for example, the Society of Obstetricians and Gynaecologists of Canada (SOGC), the Society of Obstetric Medicine of Australia and New Zealand (SOMANZ), and the National College of French Obstetricians and Gynecologists (CNGOF) consider the PCR to be positive when it is at 30 mg/mmol or higher, the American College of Obstetricians and Gynecologists (ACOG) when it is 0.3 mg/dL or higher (≈33.9 mg/mmol), and the Royal College of Obstetricians and Gynaecologists (RCOG) when it is over 0.3 mg/dL. These recommendations are based on numerous studies suggesting that the PCR is a good alternative to the 24HP in pre‐eclampsia . There is still controversy with some studies concluding that, on the contrary, it is not a proper diagnostic test, because of poor sensitivity and specificity or poor correlation with the 24HP due to the variety of results of the PCR over a 24‐hour period .…”
Section: Discussionmentioning
confidence: 99%